The alfalfa cultivars evaluation in the region of Lavras, Minas Gerais, Brazil - Moreira, Adônis; Evangelista, Antônio Ricardo; Rodrigues, Geraldo Hélcio Seoldo (Pesquisa Agropecuaria Brasileira, 1996)
This work evaluated the adaptation of nine cultivars of alfalfa in the Lavras region of Minas Gerais, Brazil. The experiment was carried out in a Dystrophic Dusky Red Latosol (Oxisol). The experimental design consisted of a randomized complete block with four replications. The analysed variables were: dry matter production, total dry matter, levels and amounts of crude protein, and the seasonal influence of alfalfa production and quality. Based on the obtained results, the cultivars CUF 101, Florida 77, INIA, Sudam, P5929 and UC Cibola showed a significant difference from the other cultivars. The field dry matter and crude protein levels did not differ statistically. In view of the crude protein quantity in the dry matter, utilization of the cultivars AZ Lew and Mesa Sirso is not recommended in the region of Lavras. In regard to season, highest production occurred in Summer and lowest in Winter and Autumn. The analysed variables indicated a production and nutritive value comparable to those obtained on temperate and tropical climate regions.